KEHADIRAN ANGKLUNG PENTATONIK RAGAM LARAS SEBAGAI INOVASI PERTUNJUKAN MUSIKAL BUDAYA SUNDA DI JAWA BARAT - Endah Irawan dkk. (LP2M ISBI Bandung, 2018)
Angklung became part of traditional music that develop in the agrarian society in Sundanese culture and Nusantara, Indonesia. This musical instrument is environmentally friendly, has a distinctive sound, communal, practical, can be play by people at wide age range, and very suitable for educational tools. The experiment of